(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: In this study, drawing on social learning theory, a moderated mediation model was tested. This model examines organizational identification as the mediator and employee unethical tolerance as the moderator in relationships between leader-member exchange (LMX) and unethical pro-organizational behaviors (UPB). Methodology: The research sample is comprised of 432 full-time employees of a private company operating in the service sector in Turkey. Results: Consistent with the theoretical model, analysis results indicate that organizational identification mediated a positive relationship between LMX and UPB. Furthermore, results supported the moderated mediation model and showed that an indirect effect of LMX on UPB through organizational identification is stronger when EUT is high rather than low. Conclusion: This study contributes to LMX and UBP literature by integrating research on organizational identification and employee unethical tolerance.